Bacterial vaginosis and the role of prebiotics and probiotics: current practices - Gupta, Mukesh; Tiwari, Brajbala (International Journal of Research in Medical Sciences, 2024)
Bacterial vaginosis (BV) is characterized by overgrowth of opportunistic bacteria and a decrease in the levels of Lactobacilli. BV is commonly encountered by gynaecologists practicing in India. The opinions of 21 gynaecologists across India regarding diagnosis and management of BV were sought via focussed group discussions. In Indian women, BV is more common in the reproductive age group, perimenopausal women, women with polycystic ovarian disease (PCOD), pregnant women, and in teenagers/pubertal age group. BV is often underestimated as it is not diagnosed by family physicians. The panel of experts opined that they preferred to conduct screening for BV in all high-risk pregnant cases, women with bad obstetric history such as premature abortions and women with a history of tuberculosis. One challenge faced by clinicians in the real-world setting is recurrent infections of BV in their patients. For the treatment of BV, antibiotics can be prescribed along with pre-probiotics to avoid dysbiosis and to prevent recurrence of BV. Pre-probiotics should be administered in sufficient amounts for adequate management of BV. More than 80% of Lactobacilli species should be present in an ideal pre-probiotic to ensure adequate production of acid and bacteriocins for the destruction of unhealthy bacteria and prevention of microfilm formation. The results with the pre-probiotics used will depend on the quality of the formulation and the maintenance of the cold chain. Prebiotic -probiotic supplementation may be considered a new adjuvant treatment for BV.